Mandibular First and Second Molars with Three Mesial Canals: A Case Series - Aminsobhani, Mohsen; Bolhari, Behnam; Shokouhinejad, Noushin; Ghorbanzadeh, Abdollah; Ghabraei, Sholeh; Rahmani, Mohamad Bagher (Iranian Endodontic Journal, 2010)
Adequate cleaning, shaping and filling of the root canal system are mandatory for successful root canal treatment. Thorough knowledge of root canal morphology and unusual anatomy of the tooth is critical for the practitioner. The occurrence and location of the third mesial canal (Middle Mesial Canal) in mandibular first and second molars in relation to other two mesial canals that were treated in private practice were studied. In 27 clinical cases, the presence of a middle mesial canal was demonstrated. The third canal was located in the middle of the distance between the mesiobuccal and mesiolingual canals. This canal configuration was found in six second lower molars and twenty one first molars. Middle mesial canal in all of our cases joined to mesiobuccal or mesiolingual canals. None of the teeth consisted of three independent canals with three apical foramina. In conclusion, every attempt should be made to find and treat all root canals of a tooth.